2019
DOI: 10.1128/mbio.01945-19
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Outbreak-Causing Carbapenem-Resistant Klebsiella pneumoniae ST258 at a Tertiary Care Hospital over 8 Years

Abstract: Carbapenem-resistant Klebsiella pneumoniae (CRKP) strains belonging to sequence type 258 (ST258) are frequent causes of hospital-associated outbreaks and are a major contributor to the spread of carbapenemases. This genetic lineage emerged several decades ago and remains a major global health care challenge. In this study, genomic epidemiology was used to investigate the emergence, evolution, and persistence of ST258 carbapenem-resistant K. pneumoniae outbreak-causing lineages at a large tertiary care hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 53 publications
6
77
0
Order By: Relevance
“…This feature agrees with what has been reported for plasmids and actinobacteriophages that encode homologs of H-NS and Lsr2, respectively, which have a lower GC content compared with those which do not encode an XS homolog [63]. The low GC of the EARL islands and its narrow range of variability (35.7-39.2%) could be the result of their relatively rapid spread within Enterobacteriaceae, an idea supported by the fact that ROD21 can be transferred by conjugation [106] and that the ICEKp258.2 island from K. pneumoniae ST258, which may represent an early member of the SpnT/type-3 R-M-encoding clade within the EARL phylogeny [50], was acquired by this sequence type approximately 20-25 years ago [120][121][122]. Since the XSs show preference for AT-rich DNA, we speculate that these elements have a selective pressure to acquire genes encoding factors that could interact with the silencing effectors from the host cell in order to relieve silencing and provide the opportunity to be incorporated in the host regulatory network.…”
Section: The Enterobacteriaceae-associated Rod21-like Genomic Islandsmentioning
confidence: 98%
“…This feature agrees with what has been reported for plasmids and actinobacteriophages that encode homologs of H-NS and Lsr2, respectively, which have a lower GC content compared with those which do not encode an XS homolog [63]. The low GC of the EARL islands and its narrow range of variability (35.7-39.2%) could be the result of their relatively rapid spread within Enterobacteriaceae, an idea supported by the fact that ROD21 can be transferred by conjugation [106] and that the ICEKp258.2 island from K. pneumoniae ST258, which may represent an early member of the SpnT/type-3 R-M-encoding clade within the EARL phylogeny [50], was acquired by this sequence type approximately 20-25 years ago [120][121][122]. Since the XSs show preference for AT-rich DNA, we speculate that these elements have a selective pressure to acquire genes encoding factors that could interact with the silencing effectors from the host cell in order to relieve silencing and provide the opportunity to be incorporated in the host regulatory network.…”
Section: The Enterobacteriaceae-associated Rod21-like Genomic Islandsmentioning
confidence: 98%
“…One study reported that the transmission rate of ESBL-producing organisms was 2-fold higher from patients colonized with K. pneumoniae than from those colonized with E. coli (335). Large-scale nosocomial outbreaks have been caused by highly virulent and transmissible isolates of ESBL-and carbapenemase-producing strains, such as E. coli ST131 and K. pneumoniae ST258 (209,336). Although most outbreaks of ␤-lactamase producing Enterobacteriaceae occur in the ICU or in immunocompromised patients, neonates can also be affected.…”
Section: Transmission Of ␤-Lactamase-producing Pathogensmentioning
confidence: 99%
“…While K. pneumoniae sequence type (ST) 258 has been recognized as antibiotic-resistant, high-risk clonal lineage [9], ST307 came into spotlight only more recently [3,10,11]. The first K. pneumoniae ST307 isolates were obtained in the Netherlands in 2008 and Pakistan in 2009, followed by a period of sporadic isolations across Europe, Asia, Africa, and the Americas [11], and originated mostly, but not uniquely, from clinical samples [3,10].…”
Section: Introductionmentioning
confidence: 99%